Modified turn-up technique for proximal anastomosis in acute aortic dissection type A has potential to facilitate stable outcomes for low-volume early-career surgeons - Tsutsui, Masahiro; Ishidou, Kouhei; Narita, Masahiko; Usioda, Ryohei; Kikuchi, Yuta; Shirasaka, Tomonori; Ishikawa, Natsuya; Kamiya, Hiroyuki (Frontiers in Surgery, 2022)
Objective: Secure proximal anastomosis is an essential part of surgical treatment for acute aortic dissection type A (AADA). This study aimed to investigate the effectiveness of the modified turn-up technique for proximal anastomosis in AADA and compare this technique with other techniques. Methods: We divided 57 patients who underwent ascending aorta replacement for AADA into the modified turn-up technique group (Group A: 36 patients) and other technique group (Group B: 21 patients). Intraoperative and postoperative course data were compared between Groups A and B. In Group A, we also compared early-career surgeons (practicing for <10 years after graduation) and aged surgeons (practicing for >=10 years after graduation). Results: Preoperative patient characteristics did not differ between groups. There was a tendency toward shorter operation time in Group A than Group B without statistic significant (P=0.12), and the length of intensive care unit stay was significantly shorter (p<0.01) and the occurrence of cerebral infarction fewer (p<0.01) in Group A than Group B, whereas mortality and major complication other than cerebral infarction rate did not differ between groups. In Group A, 13 patients were operated by early-career surgeons and 23 patients were operated by surgeons with more than 10-year experience. Aortic clamp time and circulatory arrest time were significantly longer in patients operated by early-career surgeons, but outcomes were comparable. Conclusions: The modified turn-up technique was comparable to other techniques. Even for less skilled surgeons (e.g., early-career surgeons), the use of this technique may lead to stable outcomes.